Wodzirej - Falk, Feliks (Poland, 1978)
The stakes are very, very small for Danielak (Jerzy Stuhr), but a "careerist" doesn't measure these things. He wants an upcoming job as the dance leader and master of ceremonies for the opening ceremonies at a new provincial hotel's nightclub, and he will do anything to get it, including betraying his best friend.
Keywords: Fiction films